ASIMETRI INFORMASI DAN UNDERPRICING : STUDI EMPIRIS DI BURSA EFEK INDONESIA - Teti Anggita Safitri (Jurnal Manajemen Sinergi, 2014)
The initial public offering is an activity made by the company in event of the public offering of stock sales. The shares listed on the primary market aregenerally enthused by the investors because they give a high initial return. Thisreturn indicates the occurence of underpricing in the primary market.Underpricing is a condition in which the share price at the time of offering isrelatively too cheap compared to price in the secondary market. The aim of thisresearch is to examine the effect of assymetric information on underpricing.This research used a sample of 63 companies that make initial public offering onthe Indonesia Stock Exchange in the period of 2005-2010. The data analysis isusing multiple linear regression, which is testing the proxy of asymmetricinformation which consists of the firm size, the firm age, the proportion of sharesoffered to the public, underwriter reputation and auditor reputation onunderpricing.This research indicates that underwriter reputation and auditor reputation have asignificant effect on underpricing. Meanwhile, the firm size, the firm age and theproportion of shares offered to the public have no significant effect onunderpricing.